PREDICTING TOURSTS’ INTENTION TO VISIT BOGOR BOTANICAL GARDEN - Hana Zyadzya; Usep Suhud; Agung Kresnamurti Rivai P (JELAJAH: Journal of Tourism and Hospitality, 2020)
This study aims to measure the factors that influence the intention of tourists to the Bogor Botanical Gardens as a tourist destination by using tourists, the value received by tourists, tourist satisfaction, tourist experience as a predictor. Data was collected using Google forms. This research was conducted in Jakarta, Indonesia involving 254 respondents consisting of 189 women (74.4%) and 65 men (25.6%). Data were analyzed using exploratory factors and models. The results show that tourist motivation is positively and significantly influenced by the perceived value of tourists, tourist motivation was positively and significantly influenced by tourist satisfaction, tourist motivation is positively and significantly influenced by tourist experience, the perceived value of tourists has no effect on the intention of revisiting, satisfaction positive and significant tourists are influenced by the intention to visit again, the experience of tourists does not affect the intention to visit again, and the motivation of tourists does not affect the intention to visit again.